Does athletic identity enhance subjective wellbeing among elite collegiate athletes in team sports? A sequential mediation model of perceived team support and self-efficacy - Cui, J.; Zhang, M.; Han, Y.; Chai, W. (Frontiers in Psychology, 2026)
To investigate the mediating roles of perceived team support and self-efficacy in the relationship between athletic identity and subjective wellbeing among elite collegiate athletes in team sports. A total of 309 valid questionnaires were collected from athletes across six universities in China. Structural equation modeling and bootstrap analysis were employed to test the sequential mediation model. Athletic identity exhibited a significant positive effect on subjective wellbeing. Perceived team support and self-efficacy independently mediated this relationship, while their sequential mediation effect was also significant. Perceived team support and self-efficacy sequentially mediated the positive association between athletic identity and subjective wellbeing. These findings highlight the importance of fostering supportive team environments and enhancing self-efficacy to promote mental health and holistic development in elite collegiate team-sport athletes.